Physiopathology and prospectives for therapeutic treatment of pulmonary fibrotic state in COVID-19 patients - Antonio Vitiello; Francesco Ferrara (Elsevier, 2021)
The COVID-19 global pandemic has caused about 4,30 Mln deaths. Recently the first vaccines have been licensed, representing the most powerful weapon available to stop the pandemic. The COVID-19 viral infection in the most severe cases can cause severe lung lesions with the presence of ﬁbrotic tissue. Even among cured individuals, the presence of pulmonary fibrotic tissue may be the major cause of long-term complications of COVID-19 requiring antifibrotic therapeutic treatment even in the post-COVID-19 infection phase to accelerate the healing process and fully recover lung function. This article reviews the fibrogenic mechanism of SARS-CoV-2-induced viral damage and the antifibrotic treatments indicated to treat sequelae post COVID-19 infection.